Advances in Osteoporosis - Dionyssiotis, Yannis (IntechOpen, 2015)
A balanced regulation of bone formation and resorption in the healthy individual is required for a healthy bone. On the other side, there are many factors which can lead to alterations in bone density and microarchitecture. Menopause is a condition which can increase the remodeling process in favor of resorption. Moreover, there are also some diseases, i.e. chronic kidney bone disease, that increase the possibility of fractures and the subsequent disability leading to increased mortality. However, it is clear that drugs are an essential element of the therapy and this issue is analyzed extensively in this book. Some novel pathophysiological mechanisms are also presented, offering advanced knowledge to the reader. The book includes chapters from scientific departments and researchers from all over the world.